A educação de crianças e adolescentes acolhidos em casas abrigo - Santos, Diego Fernando (Universidade Federal de São Carlos, 2025)
This research aims to present a study based on interviews conducted with seven subjects who spent part or all of their childhood, adolescence, and/or youth in foster care institutions. The overall objective was to investigate, through their narratives, the processes of formal and informal education and the role and articulation of the ECA (Child and Adolescent Statute) and SUAS (Unified Social Assistance System) in the lives of the subjects and in foster care institutions in the municipality of São Carlos (SP) from 1990 to 2010. The research has a qualitative approach and fieldwork, based on Oral History as a method of data construction. This work is supported by theories of the history of childhood and the history of Brazilian education, with the author Mary Del' Priore (2002) and the author Amarílio Ferreira Junior (2010) as pillars. It concludes that school and non-school education are elements of resistance, overcoming, and reinvention of the individuals themselves, who, despite adverse conditions, through formal and informal support networks and their own daily coping strategies, managed to build life projects, identities, and trajectories of personal, professional, and social development. Furthermore, it is concluded that, although the legal frameworks of the ECA and SUAS represented undeniable advances in the field of children's and adolescents' rights in Brazil, there are still significant challenges between the legislation and its effective application in the daily lives of foster care institutions and in the lives of children and adolescents in institutional care.
The education of children and adolescents in shelter homes
Keywords: Educação; Crianças e adolescentes; ECA/SUAS; Memória; Oral history; Children and adolescents; Memory; CIENCIAS HUMANAS::EDUCACAO::ADMINISTRACAO EDUCACIONAL::ADMINISTRACAO DE SISTEMAS EDUCACIONAIS; 4. Educação de Qualidade